Evaluation of interseeded grain sorghum and soybeans as a silage crop - S.H.M. Esmail; K. Bolsen; S. Azimi; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1988)
Interseeded grain sorghum and soybeans were harvested at late-boot, milk, and late-dough maturity stages of the sorghum (62, 77, and 91 days post-planting, respectively). Maximum dry matter yield occurred at the late-dough stage and interseeded silages had higher crude protein contents than the control, late-dough) grain sorghum silage. All silages underwent normal homolactic fermentations and were well preserved. Cellulose and acid detergent fiber contents were also higher in the mixtures than in the control silage, but fiber values decreased as maturity advanced. Digestibilities of most nutrients were similar in the rations, but when considered with chemical composition and yield data, late-dough harvest maximized utilization of the interseeded sorghum-soybean silage. Response to the silage inoculant Biomate® was determined in laboratory silos, and the greatest benefit occurred in the milk stage silage. Cattle fed the late-dough stage grain sorghum control silage had faster (P<.05) gains and higher intakes than those fed the late-dough sorghum-soybean silage. Adding grain improved gain and intake only for cattle fed the interseeded silage. In a subsequent trial, seeding grain sorghum and soybeans in alternating 15-inch rows increased the proportion of soybean plants and crude protein in the mixture at the late-dough harvest, with similar dry matter yields.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Interseeded grain sorghum; Soybeans; Silage